2022
DOI: 10.1186/s43088-022-00284-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of curcumin-loaded liposomes in lysine–collagen hydrogel for surgical wound healing

Abstract: Background A surgical wound is an incision made by a surgeon. Slow surgical wound healing may lead to chronic wounds which may be a potential health problem. The aim of this study is to formulate curcumin-loaded liposomes in lysine–collagen hydrogel for enhancing surgical wound healing. Curcumin-loaded liposomes were prepared using thin-film hydration method. The liposomal formulation was characterized by analysing its size, morphology, encapsulation efficiency, and in vitro release. The hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Cardoso-Daodu et al succeeded in formulating lysine–collagen hydrogel-containing curcumin-loaded liposomes. In vivo results on 15 male Wistar rats, weighing 350–400 g, showed that after 3 days of the surgical procedure, the nanohydrogel formulation had the highest percentage wound contraction and closure of 79.25% compared to the control group, which showed complete closure by day 14 post-surgery with obvious scarification [ 104 ].…”
Section: Curcumin-loaded Delivery Systems For Wound Healingmentioning
confidence: 99%
“…Cardoso-Daodu et al succeeded in formulating lysine–collagen hydrogel-containing curcumin-loaded liposomes. In vivo results on 15 male Wistar rats, weighing 350–400 g, showed that after 3 days of the surgical procedure, the nanohydrogel formulation had the highest percentage wound contraction and closure of 79.25% compared to the control group, which showed complete closure by day 14 post-surgery with obvious scarification [ 104 ].…”
Section: Curcumin-loaded Delivery Systems For Wound Healingmentioning
confidence: 99%
“…The data showed that hydrogels containing LP had the highest percentage of wound contraction, presenting epidermis and dermis layers with a normal physiological structure. Corroborating these findings, the histomorphometric values showed the highest percentage of collagen, lowest inflammatory rates, highest presence of microvessels, and reepithelization rates at the wound site in animals treated with nano-based formulation [ 91 ]. Given the great water adsorption, bioadhesive property, and sustained release of the actives from the nano-based hydrogel, the wound healing of rats was greatly enhanced in comparison to the other groups, suggesting that the association of phytochemical with LP can greatly promote the rate of wound healing.…”
Section: Soft Nanoparticles and Hydrogels For Wound Healingmentioning
confidence: 96%
“…Similarly, curcumin has been shown to possess relevant wound-healing properties, by improving granulation tissue formation, collagen deposition, tissue remodeling, and wound contraction [ 131 ]. Hydrogels containing LP of quercetin [ 67 ] or curcumin [ 91 ] were already investigated as potential healing enhancer candidates. The nanocarriers were composed of phosphatidylcholine and produced using the thin lipid film hydration method.…”
Section: Soft Nanoparticles and Hydrogels For Wound Healingmentioning
confidence: 99%
See 2 more Smart Citations